2020
DOI: 10.1161/strokeaha.120.029517
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Brain

Abstract: Background and Purpose: An important minority of cerebral small vessel disease (cSVD) is monogenic. Many monogenic cSVD genes are recognized to be associated with extracerebral phenotypes. We assessed the frequency of these phenotypes in existing literature. Methods: We performed a systematic review following the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), searching Medline/Embase for publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Mutated COL4A1 disrupts the basic structure of cerebral small vessels via a dominant-negative effect or haploinsufficiency, which results in autosomal-dominant cerebral small-vessel disease 1 , 2 . Approximately 60% of patients with COL4A1 -related disorders present with diffuse white matter lesions, 50% with microbleeds, and 10–30% with hemorrhagic stroke 3 , 4 . The high incidence of intracerebral hemorrhage illustrates the clinical differences from other hereditary cerebral small-vessel diseases, such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL), and hereditary endotheliopathy, retinopathy, nephropathy, and stroke (HERNS) 3 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Mutated COL4A1 disrupts the basic structure of cerebral small vessels via a dominant-negative effect or haploinsufficiency, which results in autosomal-dominant cerebral small-vessel disease 1 , 2 . Approximately 60% of patients with COL4A1 -related disorders present with diffuse white matter lesions, 50% with microbleeds, and 10–30% with hemorrhagic stroke 3 , 4 . The high incidence of intracerebral hemorrhage illustrates the clinical differences from other hereditary cerebral small-vessel diseases, such as cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL), and hereditary endotheliopathy, retinopathy, nephropathy, and stroke (HERNS) 3 .…”
mentioning
confidence: 99%
“…To date, more than 350 patients and 70 pathogenic and likely pathogenic variants have been reported 5 . The phenotypic spectrum of COL4A1 -related disorders has been expanding, and accumulating data have shown that extracerebral hemorrhages may also occur 4 . Moreover, the coexistence of neural tumors has been observed 6 .…”
mentioning
confidence: 99%
See 3 more Smart Citations